KELENGKAPAN STATUS IMUNISASI TETANUS TOXOID PADA IBU HAMIL - Anggraini, Lola; Yunita, Jasrida; Jepisah, Doni; Ismainar, Hetty; Megasari, Miratu (Ensiklopedia of Journal, 2024)
Tetanus Toxoid Immunization in pregnant women or women of childbearing age can reduce the risk of Neonatal Tetanus incidence by 94%, making Tetanus Toxoid Immunization one of the main strategies in the successful implementation of the Elimination of Maternal and Neonatal Tetanus (ETMN) program. The percentage of coverage of pregnant women who received Td2 + was 42.8%. This is still far from the set target of 80%.  The aim was to analyze the factors associated with Tetanus Toxoid Immunization status in third trimester pregnant women at UPT Puskesmas Tembilahan Kota, Indragiri Hilir Regency. The research method used quantitative research methods with a Cross Sectionl design approach. The number of samples in this research amounted to 175 people. Data collection through primary data by distributing questionnaires. The results of this research indicated that there was a relationship between knowledge (p value = 0.008), attitude (p value = 0.010), occupation (p value = 0.011), parents in law or family support (p value = 0.005), health worker support (p value = 0.001), exposure to premarital counseling (p value = 0.046), social culture (p value = 0.007), the role of the KUA sector (p value = 0.003) with the completeness of TT immunization in third trimester pregnant women at the Tembilahan City Health Center. Conclusion, the variable role of the KUA sector is the dominant factor that most influences pregnant women in getting complete TT immunization with p value = 0.01, r2 = 0.252, and OR = 2.727. Suggest, the role of the KUA sector can be improve and cooperate with other cross-sectors, such as the RT / RW level, the Headman / and the Sub-district in monitoring and encouraging the society to check reproductive health including Tetanus Toxoid Immunization status.Keywords        : Factor, Tetanus Toxoid Immunization, Pregnant Mother